Energy, exergy, economy analysis and geometry optimization of spiral coil heat exchangers. (February 2023) - Zeinali, Salar; Neshat, Elaheh
Abstract: The present investigation deals with the exergy and exergoeconomic study of a heat exchanger with a shell and spiral tube, considering different geometries. The Realizable k-ε turbulent model is employed to simulate the heat exchanger and irreversibility calculation in the shell and spiral tube. The numerical results in this study are validated through experimental data from previous research. The influences of the different geometrical parameters on purchased equipment cost, heat exchanger irreversibility as well as efficiency of the second law are investigated. These parameters include the coil pitch, the minimum radius of the spiral, coil radius, shell thickness, and shell radius. It is realized that heat transfer is the primary source of exergy destruction. Increasing coil pitch from 20 to 40 mm results in a reduction of, on average, 4% of the second law efficiency of the heat exchanger and 3.54% increase in purchased equipment cost value. Similarly, increasing the coil radius comes up with a reduction by about 19% of the heat exchanger efficiency. Moreover, investigating the influence of studied geometrical parameters on purchased equipment cost reveal that the most and least effective geometrical parameters are coil radius and minimum radius of spiral, respectively.